MicroRNA Expression Profiling in Age-Dependent Renal Impairment - Yanai, Katsunori; Kaneko, Shohei; Ishii, Hiroki; Aomatsu, Akinori; Hirai, Keiji; Ookawara, Susumu; Morishita, Yoshiyuki (Frontiers in Medicine, 2022)
Background: Age-dependent renal impairment contributes to renal dysfunction in both the general population and young and middle-aged patients with renal diseases. Pathological changes in age-dependent renal impairment include glomerulosclerosis and tubulointerstitial fibrosis. The molecules involved in age-dependent renal impairment are not fully elucidated. MicroRNA (miRNA) species were reported to modulate various renal diseases, but the miRNA species involved in age-dependent renal impairment are unclear. Here, we investigated miRNAs in age-dependent renal impairment, and we evaluated their potential as biomarkers and therapeutic targets. Methods: We conducted an initial microarray profiling analysis to screen miRNAs whose expression levels changed in kidneys of senescence-accelerated resistant (SAMR1)-10-week-old (wk) mice and SAMR1-50wk mice and senescence-accelerated prone (SAMP1)-10wk mice and SAMP1-50wk mice. We then evaluated the expressions of differentially expressed miRNAs in serum from 13 older patients (>65 years old) with age-dependent renal impairment (estimated glomerular filtration ratio <60 mL/min/1.73 m2) by a quantitative real-time polymerase chain reaction (qRT-PCR) and compared the expressions with those of age-matched subjects with normal renal function. We also administered miRNA mimics or inhibitors (5 nmol) with a nonviral vector (polyethylenimine nanoparticles: PEI-NPs) to SAMP1-20wk mice to investigate the therapeutic effects. Results: The qRT-PCR revealed a specific miRNA (miRNA-503-5p) whose level was significantly changed in SAMP1-50wk mouse kidneys in comparison to the controls. The expression level of miRNA-503-5p was upregulated in the serum of the 13 patients with age-dependent renal impairment compared to the age-matched subjects with normal renal function. The administration of a miRNA-503-5p-inhibitor with PEI-NPs decreased the miRNA-503-5p expression levels, resulting in the inhibition of renal fibrosis in mice via an inhibition of a pro-fibrotic signaling pathway and a suppression of glomerulosclerosis in mice by inhibiting intrinsic signaling pathways. Conclusion: The serum levels of miRNA-503-5p were decreased in patients with age-dependent renal impairment. However, inhibition of miRNA-503-5p had no effect on age-dependent renal impairment, although inhibition of miRNA-503-5p had therapeutic effects on renal fibrosis and glomerulosclerosis in an in vivo animal model. These results indicate that miRNA-503-5p might be related to age-dependent renal impairment.